All Days 2003
DOI: 10.2118/81723-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Low Cycle Fatigue and Plastic Strain Response of Coiled Tubing in a Sour Environment With and Without Corrosion Inhibitor Protection

Abstract: TX 75083-3836 U.S.A., fax 01-972-952-9435. AbstractThe post-yield material performance of 70 and 80 ksi yield strength carbon steel and high-strength corrosion resistant alloy (CRA) coiled tubing (CT) has been investigated experimentally to evaluate its response to a sour environment following plastic bending straining induced during coiled tubing operations. Although this investigation was specifically targeted for under-balanced drilling of sour wells, the results obtained can also be interpreted with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…It is interesting that these sour-fatigue-life values from reversebending-fatigue tests are on the same order of magnitude as those reported by Luft (2003) from uniaxial corrosion fatigue tests performed on 70-and 80-grade CT full-body samples; the sour fatigue life of samples with inhibitor (probably no internal cracking, see Effect of H 2 S Anticracking Inhibitor section) was approximately 67% of the fatigue life measured in air, while for those tests without inhibitor (probably damaged by internal cracking) the sour fatigue life was between 15 and 20% of the fatigue life measured in air.…”
Section: Pipe-body Sour Fatigue Performance-without Anticrackingsupporting
confidence: 78%
See 2 more Smart Citations
“…It is interesting that these sour-fatigue-life values from reversebending-fatigue tests are on the same order of magnitude as those reported by Luft (2003) from uniaxial corrosion fatigue tests performed on 70-and 80-grade CT full-body samples; the sour fatigue life of samples with inhibitor (probably no internal cracking, see Effect of H 2 S Anticracking Inhibitor section) was approximately 67% of the fatigue life measured in air, while for those tests without inhibitor (probably damaged by internal cracking) the sour fatigue life was between 15 and 20% of the fatigue life measured in air.…”
Section: Pipe-body Sour Fatigue Performance-without Anticrackingsupporting
confidence: 78%
“…In addition, these tests do not give data that could be related with the low-cycle fatigue performance after sour exposure; such data could be used for strings management in real operating conditions, as corresponding data are used for CT operations under sweet conditions. By 2003, uniaxial, low-cycle corrosion fatigue tests of short full-body CT samples were used to evaluate the sour fatigue performance of 70-and 80-grade CT materials (Luft 2003). Lowcycle fatigue life was measured in noninhibited and inhibited sour environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homogenous microstructure is recommended to be achieved through modify chemistries and manufacturing process [5]. Coiled tubing should be welded together with butt welding in field to get enough length, but unfortunately, its outstanding 1 Xiao LI, Kai Shi, Yanming Liu, Hongduo Wang.…”
Section: Introductionmentioning
confidence: 99%
“…For underbalanced-drilling operations in sour wells, performance testing of corrosion inhibitors demonstrated that there should always be an H 2 S inhibitor incorporated where CT is used (Luft 2003;McCoy and Thomas 2006).…”
Section: Introductionmentioning
confidence: 99%